The role of calcium channels in osteoporosis and their therapeutic potential - Hao, Ying; Yang, Ningning; Sun, Mengying; Yang, Shangze; Chen, Xingjuan (Frontiers in Endocrinology, 2024)
Osteoporosis, a systemic skeletal disorder marked by diminished bone mass and compromised bone microarchitecture, is becoming increasingly prevalent due to an aging population. The underlying pathophysiology of osteoporosis is attributed to an imbalance between osteoclast-mediated bone resorption and osteoblast-mediated bone formation. Osteoclasts play a crucial role in the development of osteoporosis through various molecular pathways, including the RANK/RANKL/OPG signaling axis, cytokines, and integrins. Notably, the calcium signaling pathway is pivotal in regulating osteoclast activation and function, influencing bone resorption activity. Disruption in calcium signaling can lead to increased osteoclast-mediated bone resorption, contributing to the progression of osteoporosis. Emerging research indicates that calcium-permeable channels on the cellular membrane play a critical role in bone metabolism by modulating these intracellular calcium pathways. Here, we provide an overview of current literature on the regulation of plasma membrane calcium channels in relation to bone metabolism with particular emphasis on their dysregulation during the progression of osteoporosis. Targeting these calcium channels may represent a potential therapeutic strategy for treating osteoporosis.